2008
DOI: 10.1002/jbm.a.32215
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and controlled release of prostaglandin E2 from poly‐L‐lactide‐co‐glycolide microspheres

Abstract: Prostaglandin E(2) (PGE(2)) is an arachidonic acid metabolite involved in physiological homeostasis and numerous pathophysiological conditions. Furthermore, it has been demonstrated that prostaglandins have a stimulating effect not only on angiogenesis in situ and in vitro but also on chondrocyte proliferation in vitro. Thus, PGE(2) represents an interesting signaling molecule for various tissue engineering strategies. However, under physiological conditions, PGE(2) has a half-life time of only 10 min, which l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We presume that this sustained release of DEX occurred through the PLGA polymer phase by controlled molecular diffusion because no significant surface changes were observed after 4 weeks of incubation 40. In a previous study, PLGA (lactide:glycolide = 85:15) particles were found to slowly degrade from within due to the formation of a superficial diffusion barrier and show nearly no superficial erosion even after 80 days in culture medium 41…”
Section: Discussionmentioning
confidence: 77%
“…We presume that this sustained release of DEX occurred through the PLGA polymer phase by controlled molecular diffusion because no significant surface changes were observed after 4 weeks of incubation 40. In a previous study, PLGA (lactide:glycolide = 85:15) particles were found to slowly degrade from within due to the formation of a superficial diffusion barrier and show nearly no superficial erosion even after 80 days in culture medium 41…”
Section: Discussionmentioning
confidence: 77%
“…It is currently unknown if this porosity is due to local solvent-entrapment and accumulation, while the PLGA continuously hardens, forming hollow structures or, some other mechanism. This structural data might explain the release profile (Brochhausen et al, 2008), which is shown in Fig. 7b, showing a burst release early on with a plateau after 24 h and decreasing release afterwards.…”
Section: Polymeric Drug Release System For Cartilage Tissue Engineeringmentioning
confidence: 73%
“…An HPLC/MS/MS method has been optimized to track the in vivo degradation of a zein porous scaffold . Recently, GC/MS was used to check the chemical structure of the enzymatic degradation products originated from PCL copolymers, and GC/MS/MS in drug release to measure the residual prostaglandin E2 (PGE2) content in biodegradable PLGA microspheres …”
Section: Bioresorbable Polymer Degradation Studies By Msmentioning
confidence: 99%